Perbandingan Kemampuan Polimer HPMC dengan Gom Arab dalam Meningkatkan Kecepatan Disolusi Tablet Karbamazepin - Rina Wahyuni; Auzal Halim; Eka Syuryani (Jurnal Farmasi Higea, 2015)
The effect of HPMC and gom arabic to do dissolution ability of carbamazepine tablets made by wet granulation has been. There are 5 formulas of carbamazepine granules, mind each formula was containing 40% w/w of carbamazepine. Carbamazepine wese coated by HPMC polymers and gom arabic by spray drying process. formula 0 countain carbamazepine with coanted HPMC and  gom arabic witle formula 1 and 2 is countain carbamazepine coated by HPMC polymers with  concentration 5% w/w and 10% w/w respectively. Formula 3 and 4 is countain  carbamazepine which counted by gom arabic with  concentration 5% and 10% respectively. The result shows that formula 2 show the highest dissolution rate 134.7133%.